Molecular and cellular designs of insect taste receptor system - Isono, Kunio; Morita, Hiromi (Frontiers in Cellular Neuroscience, 2010)
The insect gustatory receptors (GRs) are members of a large G-protein coupled receptor family distantly related to the insect olfactory receptors. They are phylogenetically different from taste receptors of most other animals. GRs are often coexpressed with other GRs in single receptor neurons. Taste receptors other than GRs are also expressed in some neurons. Recent molecular studies in the fruitfly Drosophila revealed that the insect taste receptor system not only covers a wide ligand spectrum of sugars, bitter substances or salts that are common to mammals but also includes reception of pheromone and somatosensory stimulants. However, the central mechanism to perceive and discriminate taste information is not yet elucidated. Analysis of the primary projection of taste neurons to the brain shows that the projection profiles depend basically on the peripheral locations of the neurons as well as the GRs that they express. These results suggest that both peripheral and central design principles of insect taste perception are different from those of olfactory perception.